INTERNAL KOMUNIKASI PADA PERGANTIAN SHIFT DI NOVOTEL LAMPUNG : MASALAH, DAMPAK DAN SOLUSI - Wardani, Dyah Mustika (Jurnal Public Relations (J-PR), 2020)
A hotel is a place that aims to be a stopover for some people. So that the hotel is ready for 24 hour service. Therefore hotel employees are divided into 3 filters, one of the parts that does the system shiftt is the front office. With this division of disputes it is prone to conflicts both internal and external. This research was made with the aim of identifying what conflicts usually occur, then what impact is caused by the conflict and how to find solutions to anticipate ongoing conflicts. The method used in this research is qualitative research with obesity, interviews and literature. The sample used is a hotel that has been stable in one area in Indonesia. The results of this study indicate that miscommunication between team members and guests is the most underlying factor for conflict. Has a big impact on guest satisfaction and hotel revenue.